PENGARUH TEKANAN EKSTERNAL, KETIDAKPASTIAN LINGKUNGAN, KOMITMEN MANAJEMEN DAN SISTEM PENGENDALIAN PEMERINTAH TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Satuan Kerja Perangkat Daerah Kabupaten Indragiri Hulu) - Rian Noprizal; Amries Rusli Tanjung; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to explore the influence of the external pressure, environmental uncertainty, management commitment and government internal control system to the application management financial transparency reporting at the offices in Indragiri Hulu Distict. The samples were determined based on purposive sampling technique. The respondents involved to be the sample of this study consisted of subsections head of finance, treasurer finance and financial staff working at any agencies around the SKPD office in Indragiri Hulu regency (87 respondents), where the data was collected through questionnaires distributed. The analysis is based on respondents' answers were obtained through questionnaires distributed by the researchers. Mechanical analysis using multiple linear regression analysis with SPSS. The results of this study indicated that the exsternal pressure, environmental uncertainty, management commitment, internal control system significantly affect the transparency of financial reporting. The magnitude of the effect (R2) of the external pressure, commitment of management and government internal control system to the application management financial transparency reporting was 76,6 %, While the remaining 23,4 % is influenced by other variables outside.Keywords : transparency, external pressure, environmental uncertainty, management commitment, internal control system.